Initial validity and reliability testing of the SGBA-5 - Andrew Putman; Adam Cole; Shilpa Dogra (PLoS ONE, 2025)
Background A growing body of research indicates that sex (biological) and gender (sociocultural) influence health through a variety of distinct mechanisms. Sex- and Gender-Based Analysis (SGBA) techniques could examine these influences, however, there is a lack of nuanced and easily implementable measurement tools for health research. To address this gap, we created the Sex- and Gender-Based Analysis Tool – 5 item (SGBA-5). Objectives This research aims to assess the validity and reliability of the SGBA-5 for use in health sciences research where sex or gender are not primary variables of interest. Methods A Delphi consensus study was conducted with Canadian researchers (n = 14). The Delphi experts rated the validity of each SGBA-5 item on a 5-point Likert scale each round, receiving summary statistics of other experts’ responses after the first round. A conservative threshold for consensus agreement (75% rating an item 4+ of 5) was used given the novelty of this scale’s items. Reliability was assessed through a two-armed test-retest study. The university student arm (n = 89) was conducted in-person (on paper), and the older adult arm (n = 71) was conducted online (digitally). Results The Delphi study ended after three rounds; experts reached consensus agreement on the validity of the biological sex item of the SGBA-5 (93%) and consensus non-agreement on each of the gendered aspect of health items (identity: 64%, expression: 64%, roles: 50%, relations: 57%). Both the student arm (sex item: κ=1.00,95%CI(1.00,1.00), gendered items: ICC(A,1)≥.899,95%CI(.851,.933)) and the older adult arm (sex item: κ=1.00,95%CI(1.00,1.00), gendered items: ICC(A,1)≥.865,95%CI(.772,.920)) of the test-retest study indicated that all items were reliable. Conclusions The novel SGBA-5 tool demonstrated reliability across all scale items and validity of the biological sex item. The gendered aspects of health items may be valid. Future research can further develop the SGBA-5 as a tool for use in health research.